The Effect of Income Level, Education Level, and Public Awareness on Land Building Tax Compliance - Erlani, Dhea Sylva; Sundarta, M. Imam; Azis, Azolla Degita; Rasiman, Rasiman (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2022)
This study aims to find out empirically about the effect of income level, education level and public awareness on land and building tax compliance in Benteng Village, Ciampea District. The research method used is quantitative method. The analysis prerequisite test consisted of normality and multicollinearity tests. Hypothesis testing using data analysis method, namely multiple linear regression with f test and t test between four variable data, namely data on the influence of income level analysis, education level and public awareness on land and building tax compliance. random, representing the population of taxpayers who have SPPT in Benteng Village (3118 taxpayers). The results of this study indicate that public awareness of land and building tax compliance has a significant effect on compliance with land and building taxes, this is because the people of Benteng village are very aware of land and building tax compliance.Especially for national development.